Improving Students’ Reading Comprehension Through Mind Mapping Technique (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2025)
The purpose of this research was to improve students’ reading comprehension through the implementation of Mind Mapping Technique at the eighth grade of MTs Mesra Pematangsiantar. This research used a quantitative approach with a pre-experimental design, specifically a one-group pre-test and post-test design. The population of this research was all the eighth grade students consisting of 307 students, and the sample was class VIII-2 with a total of 32 students selected through purposive sampling. The data collection was conducted by administering pre-test and post-test in the form of multiple-choice questions. The data were analyzed by using SPSS version 26.0, including frequency distribution, statistical analysis, normality test, homogeneity test, and hypothesis test. The result showed that there was a significant difference between the students’ pre-test and post-test scores after applying the Mind Mapping Technique. The result of research was Ttest (10,486) > Ttable (1,668) at the significance level α = 0.05 with the degrees of freedom (df) = (32-1=31) for one class so the degrees of freedom within groups is 62. The students’ mean score increased from 51.56 in the pre-test to 70.31 in the post-test. In the pre-test, only 4 students passed the minimum mastery criteria, while after the treatment, 15 students achieved scores above the minimum criteria.  It means that H0 is rejected and Ha is accepted. Based on the evidence from the research results, the post-test has a higher score than the pre-test. From these results it was concluded that there was a significant difference in improving students’ reading comprehension before and after being given treatment using Mind Mapping Technique as a learning technique. Therefore, it can be concluded that the use of Mind Mapping Technique significantly improved the students’ reading comprehension at the eighth grade of MTs Mesra Pematangsiantar